2017
DOI: 10.1038/srep46251
|View full text |Cite
|
Sign up to set email alerts
|

Correlations in the degeneracy of structurally controllable topologies for networks

Abstract: Many dynamic systems display complex emergent phenomena. By directly controlling a subset of system components (nodes) via external intervention it is possible to indirectly control every other component in the system. When the system is linear or can be approximated sufficiently well by a linear model, methods exist to identify the number and connectivity of a minimum set of external inputs (constituting a so-called minimal control topology, or MCT). In general, many MCTs exist for a given network; here we ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…For 38 nodes, inversion or fixation did not affect predictions in any of the cell lines. Taken together, our results support the hypothesis that a subset of nodes may be most decisive for the state of the model (Gao et al, 2014;Puniya et al, 2016;Campbell et al, 2017;Pentzien et al, 2018;Rozum and Albert, 2018;Yang et al, 2018).…”
Section: Identification Of High-influence Nodes Enables Improved Predsupporting
confidence: 86%
See 2 more Smart Citations
“…For 38 nodes, inversion or fixation did not affect predictions in any of the cell lines. Taken together, our results support the hypothesis that a subset of nodes may be most decisive for the state of the model (Gao et al, 2014;Puniya et al, 2016;Campbell et al, 2017;Pentzien et al, 2018;Rozum and Albert, 2018;Yang et al, 2018).…”
Section: Identification Of High-influence Nodes Enables Improved Predsupporting
confidence: 86%
“…Previous studies have indicated that a subset of nodes have the ability to affect the behavior of the overall network (Gao et al, 2014;Puniya et al, 2016;Campbell et al, 2017;Pentzien et al, 2018;Rozum and Albert, 2018;Yang et al, 2018). Translated to our example, this means that calibration of a set of nodes with such characteristics will determine the activity of the remaining nodes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, for other networks, some nodes are always or never in a driver set, which give a distribution of nodes in the minimum controller set. The distribution with respect to the topology of the network may be informative and characteristic of some empirical contexts [11,60].…”
Section: Is It Possible To Use Linear Controllability As a Kind Of Cementioning
confidence: 99%
“…Using the exact controllability theory [9], we calculate the minimal control set. A key feature of linear network control, which was usually not emphasized in most existing literature on linear controllability [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] but was mentioned in a recent paper [60], is that the minimal control set of nodes is not unique. For a reasonably large network (e.g., of size of a few hundred), there can be vastly many such sets that are equivalent to each other in terms of control realization.…”
Section: Introductionmentioning
confidence: 99%